Changes in primary care visits for respiratory illness during the COVID-19 pandemic: a multinational study by the International Consortium of Primary Care Big Data Researchers (INTRePID) - Westfall, John M.; Bonilla, Angela Ortigoza; Lapadula, María C.; Zingoni, Paula L.; Wong, William C. W.; Wensaas, Knut A.; Pace, Wilson D.; Silva-Valencia, Javier; Scattini, Luciano F.; Ng, Amy P. P.; Manski-Nankervis, Jo-Anne; Ling, Zheng J.; et al. (Frontiers in Medicine, 2024)
Objectives The majority of patients with respiratory illness are seen in primary care settings. Given COVID-19 is predominantly a respiratory illness, the INTernational ConsoRtium of Primary Care BIg Data Researchers (INTRePID), assessed the pandemic impact on primary care visits for respiratory illnesses. Design Definitions for respiratory illness types were agreed on collectively. Monthly visit counts with diagnosis were shared centrally for analysis. Setting Primary care settings in Argentina, Australia, Canada, China, Norway, Peru, Singapore, Sweden and the United States. Participants Over 38 million patients seen in primary care settings in INTRePID countries before and during the pandemic, from January 1st, 2018, to December 31st, 2021. Main outcome measures Relative change in the monthly mean number of visits before and after the onset of the pandemic for acute infectious respiratory disease visits including influenza, upper and lower respiratory tract infections and chronic respiratory disease visits including asthma, chronic obstructive pulmonary disease, respiratory allergies, and other respiratory diseases. Results INTRePID countries reported a marked decrease in the average monthly visits for respiratory illness. Changes in visits varied from -10.9% (95% confidence interval [CI]: -33.1% to +11.3%) in Norway to -79.9% (95% CI: -86.4% to -73.4%) in China for acute infectious respiratory disease visits and -2.1% (95% CI: -12.1% to +7.8%) in Peru to -59.9% (95% CI: -68.6% to -51.3%) in China for chronic respiratory illness visits. While seasonal variation in allergic respiratory illness continued during the pandemic, there was essentially no spike in influenza illness during the first two years of the pandemic. Conclusions The COVID-19 pandemic had a major impact on primary care visits for respiratory presentations. Primary care continued to provide services for respiratory illness, although there was a decrease in infectious illness during the COVID pandemic. Understanding the role of primary care may provide valuable information for COVID-19 recovery efforts and planning for future global emergencies.